Modes of Esports Engagement in Overwatch
XVII, 229 p. 31 illus.
Keywords: This Open Access book provides a comprehensive review of the rapidly developing esport phenomenon by examining one of its contemporary flagship titles, Overwatch (Blizzard Entertainment 2016), through three central themes and from a rich variety of research methods and perspectives. As a game with more than 40 million individual players, an annual international World Cup, and a franchised professional league with teams from Canada, China, Europe, South Korea, and the US, Overwatch provides a multifaceted perspective to the cultural, social, and economic topics associated with the development of esports, which has begun to attract attention from both commercial and academic audiences. A decade ago, it was still somewhat conventional to start a study by writing how “esports is a novel phenomenon.” As today more than a thousand studies have been published on esports, including several books and special issues, the need for more specific case studies keeps increasing. This multidisciplinary and multi-methodological book on Overwatch responds to that need. With 15 authors from various backgrounds, the book provides a far-reaching analysis of Overwatch and its modes of engagement. Ten chapters provide a foundation for understanding how a title like Overwatch operates both as an esport and a more general entertainment product at the same time. Maria Ruotsalainen is a PhD candidate at the University of Jyväskylä, Finland. Her dissertation focuses on Overwatch Esports, gender, and nationality. She has had articles published by the Men and Masculinities, European Journal of Cultural Studies, and Games and Culture. Dr. Maria Törhönen is a researcher and a project manager at Tampere University, Finland. Maria’s research focuses on the merger of work and play, especially in the context of streaming and esports. Maria is also a founding and board member of the Esports Research Network and has worked in game development prior to her academic career. Veli-Matti Karhulahti is Senior Researcher at the University of Jyväskylä, Finland, and holds an Adjunct Professorship at the University of Turku, Finland. His research tackles gaming, play, and technology use in many ways, and he is the author of Esport Play: Anticipation, Attachment, and Addiction in Psycholudic Development (2020).